Serious Illness Conversation?Evaluation Exercise: A Novel Assessment Tool for Residents Leading Serious Illness Conversations - Jenny J. Ko; Mark S. Ballard; Tamara Shenkier; Jessica Simon; Amanda Roze des Ordons; Gillian Fyles; Shilo Lefresne; Philippa Hawley; Charlie Chen; Michael McKenzie; Isabella Ghement; Justin J. Sanders; et al. (Palliative Medicine Reports, 2020)
Background/Objectives: The serious illness conversation (SIC) is an evidence-based framework for conversations with patients about a serious illness diagnosis. The objective of our study was to develop and validate a novel tool, the SIC-evaluation exercise (SIC-Ex), to facilitate assessment of resident-led conversations with oncology patients. Design: We developed the SIC-Ex based on SIC and on the Royal College of Canada Medical Oncology milestones. Seven resident trainees and 10 evaluators were recruited. Each trainee conducted an SIC with a patient, which was videotaped. The evaluators watched the videos and evaluated each trainee by using the novel SIC-Ex and the reference Calgary-Cambridge guide (CCG) at months zero and three. We used Kane's validity framework to assess validity. Results: Intra-class correlation using average SIC-Ex scores showed a moderate level of inter-evaluator agreement (range 0.523?0.822). Most evaluators rated a particular resident similar to the group average, except for one to two evaluator outliers in each domain. Test?retest reliability showed a moderate level of consistency among SIC-Ex scores at months zero and three. Global rating at zero and three months showed fair to good/very good inter-evaluator correlation. Pearson correlation coefficients comparing total SIC-Ex and CCG scores were high for most evaluators. Self-scores by trainees did not correlate well with scores by evaluators. Conclusions: SIC-Ex is the first assessment tool that provides evidence for incorporating the SIG guide framework for evaluation of resident competence. SIC-Ex is conceptually related to, but more specific than, CCG in evaluating serious illness conversation skills.